Water vapor retrieval using the Airborne Multiangle SpectroPolarimetric Imager. (June 2021) - Xu, Feng; Diner, David J.
Highlights: A two-step retrieval approach is developed to retrieve precipitable water vapor from multi-angle radiance measurements in the near-infrared. Algorithm is tested used AirMSPI instrument data. Comparison to AERONET reference data shows the mean percentage difference of precipitable water vapor amount to be 8.6%. Abstract: The Airborne Multiangle SpectroPolarimetric Imager (AirMSPI) acquires radiance measurements in eight spectral bands centered at 355, 380, 445, 470*, 555, 660*, 865*, and 935 nm, three of which also measure linear polarization (denoted by asterisks). A two-step retrieval approach is developed to retrieve total precipitable water vapor (PWV) abundance: a) the first step is a fast estimate of water vapor obtained by comparing the ratio of observed radiance in the near-infrared (NIR) bands L 935nm / L 865nm at multiple view angles against pre-calculated lookup table values as a function of PWV abundance, on the assumption of no aerosols and a moderately bright land surface; (b) the second step refines the estimated solution by accounting for aerosol loading, particle properties, and surface reflection, which are retrieved from AirMSPI measurements in its ultraviolet to NIR aerosol bands. Our retrieval is tested using 27 AirMSPI datasets with low to moderately high aerosol loadings and PWV up to about 3.5 cm, acquired during four NASA field campaigns plus one AirMSPI engineering test flight. Comparison of the retrieved total PWV amount against AERONET reference data shows a mean percentage difference 8.6%. The quantities that inform the second step of the PWV retrieval—namely, aerosol optical depth (AOD), aerosol single scattering albedo (SSA), and aerosol effective radius—are also compared to the AERONET reference data. The mean absolute differences (MADs) are less than 0.0253 and less than 0.036 for AOD and SSA in the visible, respectively. The MADs are 0.036 μm and 1.232 μm for the effective radius of fine and coarse mode aerosols, respectively. Comparison to data from the Cloud Physics Lidar places the MAD of aerosol layer height at about 360 m.